(untitled) (Medical Forum Monthly, 2021)
Objective: The purpose of this study is to compare the post-operative outcome of open cholecystectomy in spinal vs general anesthesia. Study Design: Comparative/control randomized study Place and Duration of Study: This study was conducted at the Surgery Department of Khairpur Medical College Hospital, Khairpur from January 2021 to June, 2021 for a period of six months. Materials and Methods: One hundred and twenty patients of both genders were presented in this study. Patients were aged between 18-65 years. Patients who had ASA grade I and II and underwent open cholecystectomy were presented. Detailed demographics of enrolled cases including age, sex and body mass index were recorded after taking informed written consent. Patients were equally divided into two groups. Group I had 60 patients and received spinal anesthesia for open cholecystectomy and group II received general anesthesia in 60 patients. Post-operative VAS pain score, complications, effectiveness, hospital stay and patients’ satisfaction were recorded and compared among both groups. Results: There were 35 (58.3%) male patients and 25 (41.7%) females in group I with mean age 36.18±8.76 years while in group II 33 (55%) were males and 32 (45%) females with mean age 37.13±4.88 years. Mean BMI in group I was 24.09±7.24 kg/m2 and in group II mean BMI was 25.04±4.44 kg/m2. Forty-eight (80%) cases in group I had ASA 1 and 45 (75%) patients in group II had ASA I. Mean operative time in group I was 40.03±3.61 minutes and in group II mean time was 44.07±6.18 minutes. Post- operative less pain score was observed among patients of group I 1.09±5.11 as compared to group II 3.07±4.13. Rate of complications nausea/vomiting, dizziness and hospital stay were significantly higher in group II. Recovery 48 (80%) and patients satisfaction 44 (73.3%) were higher among patients of group I as compared to group II 42 (70%) and 38 (63.3%). Conclusion: The use of spinal anesthesia in open cholecystectomy was effective as compared to general anesthesia in terms of post-operative pain, complications and hospital stay.